On the Generalization of Hilbert's Fifth Problem to Transitive Groupoids - Raźny, P. (Symmetry, Integrability and Geometry: Methods and Applications, 2017)
In the following paper we investigate the question: when is a transitive topological groupoid continuously isomorphic to a Lie groupoid? We present many results on the matter which may be considered generalizations of the Hilbert's fifth problem to this context. Most notably we present a ''solution'' to the problem for proper transitive groupoids and transitive groupoids with compact source fibers.